Det performerendes performativitet: Medie- og betydningskritik i 4’33’’ - Vandsø, Anette (Peripeti, 2021)
This article analyses the eventness of the American composer John Cages famous ‘silent piece’, 4’33’’ (1952) in order to strengthen our general conceptual understanding the artistic ’performance’, particularly its performativity.